Identification of new variants in patients with mucopolysaccharidosis in consanguineous Iranian families - Zabihi, Rezvan; Zamani, Mina; Aminzadeh, Majid; Chamanrou, Niloofar; Kiani, Fatemeh Zahra; Seifi, Tahere; Zeighami, Jawaher; Yadegari, Tahere; Sedaghat, Alireza; Saberi, Alihossein; Hamid, Mohammad; Shariati, Gholamreza; et al. (Frontiers in Genetics, 2024)
Mucopolysaccharidoses are a group of lysosomal storage disorders that include seven types that are classified based on the enzymes that are disrupted. Malfunction of these enzymes leads to the accumulation of glycosaminoglycans (GAGs) in various tissues. Due to genetic and clinical heterogeneity, diagnosing and distinguishing the different types is challenging. Genetic methods such as whole exome sequencing (WES) and Sanger sequencing are accurate methods for detecting pathogenic variants in patients. Thirty-two cases of mucopolysaccharidosis, predominantly from families with consanguineous marriages, were genetically examined. Out of these, fourteen cases underwent targeted sequencing, while the rest underwent WES. The results of WES were analyzed and the pathogenicity of the variants was examined using bioinformatics tools. In addition, a segregation analysis within families was carried out. In most cases, a pathogenic or likely pathogenic variant was detected. Sixteen previously reported variants and six new variants were detected in the known IDS (c.458G>C, c.701del, c.920T>G), GNS (c.1430A>T), GALNS (c.1218_1221dup), and SGSH (c.149T>C) genes. Furthermore, we discovered a c.259G>C substitution in the NAGLU gene for the first time in three homozygous patients. This substitution was previously reported as heterozygous. Except for the variants related to the IDS gene, which were hemizygous, all the other variants were homozygous. It appears that the high rate of consanguineous marriages in the families being studied has had a significant impact on the occurrence of this disease. Overall, these findings could expand the spectrum of pathogenic variants in mucopolysaccharidoses. Undoubtedly, genetic methods, especially WES, are very accurate and can be used alone or in conjunction with other diagnostic methods for a more precise and rapid diagnosis of mucopolysaccharidoses. Additionally, they could be beneficial for family screening and disease prevention.